Rapid-Response Unsaturated Zone Hydrology: Small-Scale Data, Small-Scale Theory, Big Problems - Nimmo, John R.; Perkins, Kim S.; Plampin, Michelle R.; Walvoord, Michelle A.; Ebel, Brian A.; Mirus, Benjamin B. (Frontiers in Earth Science, 2021)
The unsaturated zone (UZ) that extends throughout the Earth’s terrestrial surface is central to major problems of land and water management. Water flow through the UZ is typically thought to be slow and diffusive, characteristics that attenuate fluxes and dampen variability between atmospheric inputs and underlying aquifers, thereby reducing the vulnerability of water supplies to contamination and the likelihood of extreme-event hazards. In actuality, however, the spatially concentrated and rapid flow processes known as preferential flow can strongly counter these beneficial effects. Arising from the wide ranges, nonlinearity, and complexity of unsaturated hydraulic properties and processes, preferential flow is among the most poorly-characterized hydrologic phenomena. Yet it is surprisingly common and becomes more so as extreme hydroclimatic events increase in frequency and intensity. Issues of scale present additional difficulties. Unsaturated flow equations have been developed and tested based on field and laboratory measurements made at scales from pore size to plot size. Associated problems of societal concern, however—including floods, aquifer recharge, landslides, and groundwater contamination—range from watershed to regional scales. This scale disparity has spurred application of traditional model equations at coarser resolutions over larger areas than present measurements or theory can justify. Underlying this extrapolative practice is a tacit and fallacious assumption that spatially averaging slow diffusive flow and rapid preferential flow can effectively represent the influence of both processes across vast areas. Given their currently inadequate understanding and quantitative characterization, these focused and rapid processes critically need expanded attention and effort.